The Philosophy of Wabi-Sabi on Chashitsu Tai-an Myokian Shrine: A John Fiske's Semiotic Analysis - Sulistiyanie Wulan (Japanese Research on Linguistics, Literature, and Culture, 2021)
The purpose of this study is to describe the meaning of wabi-sabi that contained in the Tai-an tea room at Myokian Shrine, Kyoto Prefecture, Japan. The research of data is a video from the television program produced by NHK television station with a duration of five minutes named Hyouge Mono: Meihin Meiseki episode 7. The program features three sections of the tea room, there are nijiriguchi (the door), chashitsu (the tea room) and tokonoma (the alcove). This research used John Fiske's television semiotics theory which consists of three levels, the reality level, the representation level and the ideology level to find the codes that seen in the three sections. The method used is a qualitative descriptive method. The analysis of the reality and representation levels produces an ideology level in the form of a wabi-sabi philosophy represented by the zen aesthetic by Shinichi Hisamatsu. The results of this study indicate that in the Tai-an tea room contain several zen characteristics, there are kanso (simple), datsuzoku (free), fukinsei (asymmetric) and yugen (subtle). These characteristics represent simplicity, resignation, humility and tranquility in wabi-sabi and help to realize the concept of ichi go ichi e that aimed by Sen no Rikyu